Compact Fluorescence Lamp Based on Power Electronics Technology: its Advantages and Disadvantages - Nana Heryana; Handoko Rusiana Iskandar; Bambang Widodo; Robinson Purba (Politeknik Sukabumi, 2019)
Power-electronics based Compact Fluorescent Lamps (CFLs) have been proven to reduce electrical energy consumption for lighting purpose. As in common power-electronics-based electrical devices, CFLs can be categorized as non-linear loads. Therefore, the input current has a non-sinusoidal waveform and contains harmonics. This paper discusses the advantages and disadvantages of CFL application and proposes the attachment of THD value to the product package in order to improve the marketing policy. Total Harmonic Distortion (THD) is a method used to find the percentage value between the total harmonic components and their fundamental components. The percentage of THD causes the greater risk of damage to equipment due to harmonics that occur in current and voltage. Laboratory testing shows that a CFL sample has THD of the input current as high as 67.7%. This THD is relatively high and may degrade the electrical power quality. Moreover, it could lead to the misreading of electrical power and energy meter. Several experiment results are shown and analyzed to confirm the validity of the discussed matter.